Epidemiology of early Rapid Response Team activation after Emergency Department admission. Issue 1 (February 2016) - Mora, Juan Carlos; Schneider, Antoine; Robbins, Raymond; Bailey, Michael; Bebee, Bronwyn; Hsiao, Yu-Feng Frank; Considine, Julie; Jones, Daryl; Bellomo, Rinaldo
Summary: Background: Rapid Response Team (RRT) calls can often occur within 24 h of hospital admission to a general ward. We seek to determine whether it is possible to identify these patients before there is a significant clinical deterioration. Methods: Retrospective case–controlled study comparing patient characteristics, vital signs, and hospital outcomes in patients triggering RRT activation within 24 h of ED admission (cases) with matched ED admissions not receiving a RRT call (controls). Results: Over 12 months, there were 154 early RRT calls. Compared with controls, cases had a higher heart rate (HR) at triage (92 vs. 84 beats/min; p = 0.008); after 3 h in the ED (91 vs. 80 beats/min; p = 0.0007); and at ED discharge (91 vs. 81 beats/min; p = 0.0005). Respiratory rate (RR) was also higher at triage (21.2 vs. 19.2 breaths/min; p = 0.001). On multiple variable analysis, RR at triage and HR before ward transfer predicted early RRT activation: OR 1.07 [95% CI 1.02–1.12] for each 1 breath/min increase in RR; and 1.02 [95% CI 1.002–1.030] for each beat/minute increase in HR, respectively. Study patients required transfer to the intensive care in approximately 20% of cases and also had a greater mortality: (21% vs. 6%; OR 4.65 [95% CI 1.86–11.65]; p = 0.0003) compared with controls. Conclusions: Patients that trigger RRT calls within 24 h of admission have a fourfold increase in risk of in-hospital mortality. Such patients may be identified by greater tachycardia and tachypnoea in the ED.